Respuesta :

Answer:

[tex] \boxed{ \bold{\sf{y = 13}}}[/tex]

Step-by-step explanation:

[tex] \sf{ - 7y = - 91}[/tex]

Divide both sides of the equation by -7

⇒[tex] \sf{ \frac{ - 7y}{ - 7} = \frac{ - 91}{ - 7} }[/tex]

Calculate

⇒[tex] \sf{y = 13}[/tex]

Hope I helped!

Best regards!!

Answer:

[tex] \boxed{\sf y = 13} [/tex]

Step-by-step explanation:

Solve for y:

[tex] \sf \implies - 7y = - 91[/tex]

Divide both sides of -7y = -91 by -7:

[tex] \sf \implies \frac{ - 7y}{ - 7} = \frac{ - 91}{ - 7} [/tex]

[tex] \sf \frac{ - 7}{ - 7} = 1 : [/tex]

[tex] \sf \implies y = \frac{ - 91}{ - 7} [/tex]

[tex] \sf \implies y = \frac{ \cancel{ - 7} \times 13}{ \cancel{ - 7}} [/tex]

[tex] \sf \implies y = 13[/tex]